Sistem Informasi Inventori di Divisi EDP (Electronic Data Processing) pada PT Indomarco Prismatama Cabang Bogor 2 - Farisi, Sayyid Maulana; Kusumah, Fitrah Satrya Fajar; Al-Ikhsan, Safaruddin Hidayat (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to design and implement an inventory information system in the EDP Division of PT. Indomarco Prismatama Bogor Branch 2, which currently uses Excel to manage inventory data. The use of Excel often leads to data input errors and discrepancies between stock data and physical stock, resulting in stock shortages. The inventory information system designed using the SDLC Waterfall method is expected to minimize these errors and improve the efficiency of inventory management. The system is developed using web programming languages such as PHP, HTML, CSS, and JavaScript, and tested using the Black Box method to ensure its functionality. The results show that the implementation of this system improves the accuracy and consistency of inventory data and provides practicality in checking and counting stock in the warehouse. In addition, this system contributes knowledge in the use of web-based inventory applications and can serve as a reference for the EDP division to develop more advanced systems in the future. Suggestions for further development include expanding system access rights and integrating Android-based technology to facilitate user access.